Folk illusions : children, folklore, and sciences of perception - Barker, K. Brandon; Rice, Claiborne (Indiana University Press, 2019)
This cross-disciplinary book draws from folklore, neuroscience, and psychology to offer a detailed look at the ways children play with perception, creating what authors K. Brandon Barker and Claiborne Rice call folk illusions.